Peran Kelompok Tani dalam Meningkatkan Pendapatan Usahatani Padi Sawah di Desa Momea Kabupaten Konawe - Sarty Syarbiah; Pebrianto Pebrianto; Mahatma Putra; Pirdayanti Pirdayanti (Universitas Kristen Indonesia Toraja, 2022)
The purpose of this study was to determine the role of farmer groups in rice farming income in Momea Village, Tongauna District, Konawe Regency. The number of farmer samples was 70 farmers. The analysis used was descriptive analysis, which is a method or way of analyzing and describing existing research data, and linked to theories related to the problem in order to draw a conclusion that is presented. This data uses a Likert Scale. The role of Farmer Groups (POKTAN) in increasing rice farming income is in the moderate category. Rice farming income in Nambeaboru Village, Tongauna District, Konawe Regency averaged Rp. 7,975,376, - in the moderate category. This is due to the still high production costs and the still low harvest yields of respondent farmers. This proves that new farmer groups can play a role as production units for their members.